Burying the news for the public: Agenda cutting of the Tamil newspapers and MIC candidate Facebook during the 13th general election - Zanuddin, H.; Sern, T.J.; Ahmad, F.; Hassan, B.R.A.; Zawawi, J.W.M.; Hashim, N.; Ishak, M.B. (Universiti Kebangsaan Malaysia Press, 2017)
Guided by Agenda Cutting theory, this study examines the pattern of media coverage on issues portrayed in Tamil newspapers and Facebook during Malaysian General Election 13. A total of 1309 news articles from Tamil Nesan and Malaysia Nanban and 111 postings on MIC’s Facebook were identified and examined during the election campaign period from April 20 – May 6, 2013, specifically just before and soon after the election. A total of 127 Facebook accounts of MIC’s candidates for state and parliamentary constituencies were examined during the same period. Findings show that out of the 17 examined issues eight issues (i.e., crime, social, environment, national unity, nationalism, health issues, international relations and immigrants) were not reported by these Indian dailies. A similar result can also be found on MIC’s parliamentary and state seat candidates’ Facebook. Findings from this study draw a conclusion that without a flawed agenda cutting strategy, the MIC could have garnered valuable electoral votes during its GE13 campaign.